Improving Population Services With Application of Genetic Algorithm - Yonata Laia; Naomi Br Hutagalung; Imanuel Purba; Juli Rostianita Sitopu (LPPM Universitas Bina Sarana Informatika, 2022)
The computer system has now become one of the tools that can be used by everyone in doing work such as office work, managing family card applications, birth certificates, ID cards at the sub-district office. In this case, the problem that often occurs in the lurah office or sub-district office is the queue that is too long in the service of each community who will take care of submitting their file maker. So with that there needs to be a system that will help every employee who can minimize the performance of the person in charge of managing the file. In this research will use scheduling method with genetic algorithm. The results of the research succeeded in minimizing the waiting time by the community who would submit files at the Pancur Batu sub-district office. The time required for registration is 5 minutes per person.